Reading enhancements for students with autism spectrum disorder: A matched randomized pilot experimental study. (May 2022) - Solis, Michael; Reutebuch, Colleen; Vaughn, Sharon; Jimenez, Zaira
Abstract: Background: For students with autism spectrum disorder (ASD), improving reading comprehension is critical for increasing both their opportunities for successful postsecondary experiences including attending college and obtaining meaningful employment. The purpose of this pilot study was to investigate the effects of a multicomponent reading intervention on the vocabulary and reading outcomes of middle grade students with ASD. Method: We conducted a matched randomized pilot experimental study for students with ASD in grades 3–8 (N = 28) identified by their district personnel as having reading difficulties (i.e., not passing state reading test). An independent researcher matched participants according to symptom severity and reading fluency and then randomly assigned a member of each pair to treatment or comparison condition. Participants in treatment condition were provided 1:1 instruction for 23–30 sessions ( M  = 27) of 30 min each four to five days per week. Instructional components included (a) vocabulary instruction; (b) fluency with text, and (c) reading comprehension. In this pilot study, data were analyzed using repeated measures multilevel models in HLM 7. Due to the associated low statistical power to detect effects, the small sample size, and the exploratory nature of the study, we selected an alpha level of 0.10. Data were modeled as student-level variables classifying students based on their ASD symptomology from mild (level 1) to severe (level 3). Results: The multicomponent intervention was associated with significant gains in WJ-PC scores of 22.62 ( se  = 8.19, df  = 3, p  = .070) for students at GARS severity level 1. Significant gains favoring the intervention were also detected on vocabulary score of 10.19 ( se  = 2.78, df  = 3, p  = .035) and for students rated at GARS severity level 1 and for students rated at GARS severity level 2 [vocabulary score 5.46 ( se = 1.60, df  = 3, p  = .042)]. Significant effects were not detected for scores on a standardized measure of reading and fluency (TOSREC), and a researcher-developed measure of reading comprehension. Conclusions: This pilot study shows enough promise to warrant future studies employing larger sample sizes and fully powered randomized control trial (RCT) studies. Although growth is modest and appears to be limited to participants who are in the mid to higher range of the autism spectrum, considering the large percentage of students with ASD in the mid to higher range, this study contributes to the development of evidence-based practices. We interpret the findings as having implications for future research with larger sample sizes and in providing initial guidance on instruction for consideration by practitioners. Highlights: This pilot group design study (N = 28) investigating the efficacy of multicomponent reading intervention for students with ASD showed promise and contributed to the current literature base which is predominantly single case design studies. Instructional components included (a) vocabulary instruction; (b) fluency with text, and (c) reading comprehension. Students with mild and moderate ASD symptomology benefitted from treatment as evidenced by small gains with reading and vocabulary outcomes.